Estimating the Residential Water Demand Function - Jamshid Pazhoyan; Hosseini Seyyed Shams-Aldin (فصلنامه پژوهش‌های اقتصادی ایران, 2003)
The present paper applied Cointegration Vector Autoregressive (CVAR) Technique to Stone-Geary’s linear expenditure system، in order to estimate the residential demand for water in Metropolitan Tehran.Data used are for 1982-2000 period. Price-elasticity of the demand function is estimated as 8% for the point elasticity، and 12% for the average of duration. The income elastisities are estimated as 13% and 20%، respectively.This shows that the price elasticity of demand for water is inelastic. It is also indicated that the minimum use of water by Tehrani Citizens is 92 liters per-person per-day which is in the range of standard water use.